2003
DOI: 10.1211/002235702649
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of β-lactam antibiotics against clinical pathogens after molecular inclusion in several cyclodextrins. A novel approach to bacterial resistance

Abstract: Recognition and uptake by specific cellular receptors and transport systems for cyclodextrins have been demonstrated. Based on this concept, natural and synthetically modified cyclodextrins were used as drug carriers. Several beta-lactam antibiotics were selected and their inclusion complexes with different cyclodextrins were prepared (molar ratio ranging from 1:1 to 1:3). The complex formation, in aqueous solution, was monitored and optimum complexation conditions were selected. The inclusion of the active mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 41 publications
2
27
1
Order By: Relevance
“…The nature and degree of substitution on CD macromolecules were proposed to be the predominant factors influencing the antimicrobial activity. (Athanassiou et al, 2003) Two mechanisms for these observed effects were suggested that may have relevance to our investigation. Firstly, several outermembrane bacterial proteins similar to CymA may have facilitated the penetration of the CD-drug complexes (Pajatsch et al, 1998;1999;Orlik et al, 2003).…”
Section: Trimethoprimmentioning
confidence: 71%
See 2 more Smart Citations
“…The nature and degree of substitution on CD macromolecules were proposed to be the predominant factors influencing the antimicrobial activity. (Athanassiou et al, 2003) Two mechanisms for these observed effects were suggested that may have relevance to our investigation. Firstly, several outermembrane bacterial proteins similar to CymA may have facilitated the penetration of the CD-drug complexes (Pajatsch et al, 1998;1999;Orlik et al, 2003).…”
Section: Trimethoprimmentioning
confidence: 71%
“…Cyclodextrin (CD) complexation has been shown to alter the activity of several β-lactam antibiotics against a diverse panel of clinical isolates (Athanassiou et al, 2003). The antibacterial activities of these CDincluded antibiotics were shown to increase, particularly against Gram-negative bacteria.…”
Section: Trimethoprimmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The antibacterial activity of CD-included antibiotics was increased relative to antibiotic controls. Inclusion complex of -CD and meropenem, for example, demonstrated greater growth inhibition and stability than the uncomplexed drug.…”
Section: Cyclodextrins Loaded With Antibioticsmentioning
confidence: 99%
“…Any decrease in the ability or rate of entry and an increased export, respectively, of these compounds can lead to resistance [23,24]. In theory, augmented intracellular accumulation [31,32] and/or efflux pump inhibition could restore the susceptibility of bacteria to antibiotics; however, efflux pump inhibitors have not yet progressed into clinical use [33,34]. Furthermore, human serum interacted synergistically with ß-lactams against ß-lactamase producing Gramnegative bacteria only but not against ß-lactamase negative strains due to ß-lactamase inhibition [11,12,35].…”
Section: Introductionmentioning
confidence: 99%